Empowering the therapeutic potential of clinically expired platelet concentrates: a new source of extracellular vesicles - Meliciano, Ana Eduarda Lopes (2022)
The limited shelf-life of platelet concentrates (PC) produced in blood centers leads to a significant portion of platelet donations being discarded before being purposed for transfusion. Consequently, PC are an enormous financial burden for the healthcare system, so, new applications for expired PC have been growing over the past years. Inspired by the high amounts of platelet-derived extracellular vesicles (pEV) that are released during PC storage and by the natural appetency of pEV to interact with cancer cells, we investigated the efficacy of pEV from expired PC as carriers of paclitaxel (PTX), an anti-angiogenic and anti-cancer drug. In this thesis, pEV were isolated from expired PC using different methods (density gradient ultracentrifugation (DGUC); size exclusion chromatography and the combination of both methods). The highest EV yield (2.03x1011/100 mL PC) was obtained using DGUC, so this was selected as the most suitable protocol. Furthermore, a low level of contaminating protein, together with the detection of specific EV markers (CD9, CD63 and FLOT2) were observed. In addition, a typical EV size distribution profile (100-300 nm) with a typical cup-shaped morphology was achieved. By direct incubation, pEV were loaded with PTX (PTX-pEV), and their functionality was assessed on endothelial and breast cancer cell lines (basal, MDA-MB-231 and luminal B, BT474). Our findings suggest that PTX-pEV showed higher anti-migratory and anti-angiogenic activity than the free drug. A comparison of the cytotoxic effect of PTX-pEV on breast cancer cells was carried out, which identified a decrease in cell viability (21.05%) and proliferation (41.04%) only in BT474. PTX delivery pathways for MDA-MB-231 and BT474 were also distinctly affected by EV uptake inhibitors, between cell lines, showing that dynamin-dependent endocytosis and heparin sulphate proteoglycan- dependent mechanism were only responsible by the PTX release on BT474.